Experimental investigation of machinability parameters in high-speed micro-end milling of titanium (grade-2). Issue 9 (August 2016) - Bandapalli, C.; Singh, K.; Sutaria, B.; Bhatt, D.
Abstract This paper presents the experimental investigation of machinability parameters in high-speed micro-end milling of Ti alloy (grade-2) with uncoated tungsten carbide micro-end mills to understand the cutting mechanism and surface roughness formation. Micro-milling experiments are carried out by using a Taguchi method. The lower the better–quality characteristic in signal-to-noise ratio, analysis of variance and regression analysis are considered to analyze the effect of machining parameters on cutting forces and surface roughness. Model validation is performed by comparing analytical predicted results of cutting forces with experimental and Taguchi approach that are in good agreement. The investigation showed that micro-milling at high spindle speeds, low depth of cut, and low feed rate ensures the high quality of surface roughness and lower cutting forces.